Peran Pemuda dalam Sustainable Development Goals Kesebelas: Studi Kasus Kampung Jodipan Malang. - Adibrata, Jordan Aria; Sasmitadiharjo, Afiandi; Rahmarilla, Mawaddah Dhuha (Global and Policy Journal of International Relations, 2020)
ABSTRACTThis paper aims to explain the role of youth in overcoming the problem of slums to realize the goals of the Sustainable Development Goals number 11 formulated by the United Nations. The slum area is a classic problem in Indonesia that hasn’t resolved yet. Various strategies implemented by the government to overcome these problems have caused anxiety and refusal to be relocated. Youth people become an important factor because they have the potential to be agents of change who have creative and innovative approaches in solving problems at the social level. Moreover, in 2030 Indonesia is predicted to experience a demographic bonus, so this makes it an opportunity for this country to jump into a developed country through the role of its youth. This paper uses descriptive-qualitative methods, using data collection techniques through interviews and documentation studies. The concept of Sustainable Development Goals and the New Social Movement is an analytical tool in explaining the problem. The results obtained through the role of youths as part of a social movement that juggling slums using Creative Villages as an idea to alleviate the problems of slum areas. Jodipan Village in Malang is in the hands of young people who inspires other slum areas to transform into areas that can empower the community.Keywords: Kampung Jodipan, Youth’s role, Slum area, Sustainable Development Goals no. 11Tulisan ini bertujuan menjelaskan peranan pemuda dalam mengatasi masalah kawasan kumuh dalam mewujudkan tujuan-tujuan Sustainable Development Goals nomor 11 yang dirumuskan PBB. Masalah kawasan kumuh menjadi problem klasik di Indonesia yang belum kunjung tuntas. Berbagai macam strategi yang diterapkan pemerintah dalam mengatasi masalah tersebut justru menimbulkan keresahan serta penolakan untuk di relokasi. Pemuda menjadi aktor penting dikarenakan memiliki potensi sebagai agen perubahan yang memiliki pendekatan yang kreatif serta inovatif dalam menyelesaikan suatu permasalahan dalam level sosial. Terlebih lagi pada tahun 2030 Indonesia diprediksi akan mengalami bonus demografi, sehingga ini menjadikan sebuah peluang bagi negara ini untuk melompat menjadi negara maju melalui peran para pemudanya. Tulisan ini menggunakan metode deskriptif-kualitatif, dengan menggunakan teknik pengumpulan data melalui studi wawancara serta studi dokumentasi. Konsep Sustainable Development Goals dan Gerakan Sosial Baru merupakan alat analisa dalam menjelaskan permasalahan yang dikaji. Hasil yang didapatkan adalah melalui peran pemuda yang mengafiliasikan dirinya sebagai bagian dari gerakan sosial, berhasil mentransformasikan daerah kumuh menggunakan Kampung Kreatif sebagai ide untuk mengentaskan problem daerah pemukiman kumuh. Kampung Jodipan di Kota Malang merupakan wujud dari buah tangan para pemuda yang dapat menginspirasi daerah kumuh ain untuk bertransformasi menjadi kawasan yang dapat memberdayakan masyarakat sekitar.Kata Kunci: Kampung Jodipan, Peran Pemuda, Wilayah Kumuh, Sustainable Development Goals Nomor 11 DOI : https://doi.org/10.33005/jgp.v8i02.2416